Quantum chemical studies on the enantiomerization mechanism of several [Zn(py)3(tach)]2+ derivatives - Puchta, Ralph; Alzoubi, Basam; Meier, Roland; Almuhtaseb, Sabah I.; Walther, Markus; van Eldik, Rudi (Dalton Transactions, 2012)
The enantiomerization mechanism of the trigonal-prismatic [Zn(py)3(tach)]2+ complex and several derivatives has been studied by applying DFT calculations (B3LYP/LANL2DZp). The enantiomerization pathways of [Zn(py3tach-X)]2+ (X = C, Si, Ge, N, P, As, O, S and Se) start from a distorted trigonal-prismatic C3 symmetric ground state via an ideal trigonal-prismatic C3v structure to end up in a C3′ symmetric image of the ground state. The activation energy and structural data of the complexes depend on electronic and steric factors. The activation barriers of the complexes decrease in the order [Zn(py3tach-Ge)]2+ > [Zn(py3tach-Si)]2+ > [Zn(py3tach-As)]2+ > [Zn(py3tach-Se)]2+ > [Zn(py3tach-P)]2+ > [Zn(py3tach-S)]2+ > [Zn(py3tach-C)]2+ > [Zn(py3tach-N)]2+ > [Zn(py3tach-O)]2+ . © 2012 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2026-01-22